The Role of Family in Caring for Critically Ill Children in the Intensive Care Unit: A Narrative Review - Sri Hendrawati; Nenden Nur Asriyani Maryam; Windy Rakhmawati; Septa Permana (LP3M Universitas Muhammadiyah Tasikmalaya, 2025)
Critically ill children admitted to intensive care units experience complex physical and emotional challenges, not only for themselves but also for their families. Family-centered care (FCC) has become a cornerstone in children's critical care, emphasizing collaboration, respect, and shared decision-making between healthcare teams and families. Despite growing recognition of its benefits, the practical roles of families in children's intensive care unit settings remain diverse and sometimes underutilized across different healthcare systems and cultural contexts. This research aims to identify the family's role in caring for critically ill children in the intensive care unit. This research method uses narrative review. Articles were collected from Pubmed, ScienceDirect, EBSCOhost, and Google Scholar. The keywords used were critically ill children OR children in PICU OR children in NICU AND family involvement OR role of family OR family participation OR family-centred care OR FCC AND intensive care unit OR critical care with boolean